2016
DOI: 10.1016/j.cropro.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated rainfall on the effectiveness of insecticides against spotted wing drosophila in blueberries

Abstract: The current spotted wing drosophila, Drosophila suzukii Matsumura (Diptera: Drosophilidae) management strategy relies on routine application of insecticides during the fruit ripening and harvesting period. The amount and frequency of insecticide spray needed to maintain continuous protection of fruits may depend on a variety of factors including the level of rainfall. Studies were conducted to determine the effects of simulated rainfall (0, 12.5, 25 and 37.5 mm) and adjuvant-Nu Film (with and without) on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 20 publications
3
33
0
1
Order By: Relevance
“…However, rainfall, particularly in the first week of the experiment did coincide with the poor efficacy of insecticides as seen in the consistently high infestation in fruit. The efficacy of spinosad was previously shown to be significantly reduced by simulated rainfall between 12.5 and 25 mm (Gautam et al., ). Effective insecticide treatments in this experiment significantly reduced the number of larvae in infested fruit, with some treatments reducing the number of third instar larvae of D. suzukii in fruit.…”
Section: Discussionmentioning
confidence: 97%
“…However, rainfall, particularly in the first week of the experiment did coincide with the poor efficacy of insecticides as seen in the consistently high infestation in fruit. The efficacy of spinosad was previously shown to be significantly reduced by simulated rainfall between 12.5 and 25 mm (Gautam et al., ). Effective insecticide treatments in this experiment significantly reduced the number of larvae in infested fruit, with some treatments reducing the number of third instar larvae of D. suzukii in fruit.…”
Section: Discussionmentioning
confidence: 97%
“…In a rain fastness study, Gautam et al () observed that the effectiveness of insecticides, including spinosad, declines rapidly in the field even in the absence of rainfall. The addition of P1M did not improve residual activity (Gautam et al, ). The adjuvant PEPMS had significant effects on adult mortality with C. subtsugae and spinosad and on progeny with azadirachtin + pyrethrins and C. subtsugae .…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila suzukii adults used in bioassays were taken from separate laboratory colonies established by each collaborating university. Cultures were maintained on a standard cornmeal‐molasses (or cane sugar)‐yeast medium (Gautam et al, ; Jaramillo, Mehlferber, & Moore, ). Adults used in bioassays were 4–10 days old and were not starved prior to use in bioassays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations